The integration of character education in junior high schools during the 5.0 industrial revolution: a case study in Yogyakarta - Roidah Lina; Qiyadah Robbaniyah (At Turots: Jurnal Pendidikan Islam, 2024)
This research examines the application of character education values ​​in the Industrial Revolution 5.0 era at four junior high schools in Yogyakarta: SMP Negeri 2 Wonosari, SMP Muhammadiyah 1 Yogyakarta, SMPN 2 Berbah, and MTS Islamic Education Center Muharrikun Najaah. Using qualitative methods and case studies, data was collected through interviews, observation and documentation. The results of the research are that SMP Negeri 2 Wonosari, SMP Muhammadiyah 1 Yogyakarta, SMP Negeri 2 Berbah, and MTS Islamic Education Center Muharrikun Najaah have made great efforts in implementing the values ​​of character education in the 5.0 era with various strategies and challenges faced. At SMP Negeri 2 Wonosari, the emphasis on technological adaptation and social dynamics supports character education that is relevant in the digital era, despite facing resistance from students and parents. SMP Muhammadiyah 1 Yogyakarta implements the values ​​of faith and piety, mutual cooperation, creativity and critical thinking through the independent curriculum program, even though the challenges of globalization and social media remain. At SMP Negeri 2 Berbah, the application of character values ​​through daily and extracurricular activities faces the challenges of cultural adaptation and limited resources, while MTS Muharrikun Najaah emphasizes character formation through religion and technology-based education, although digital influences and globalization remain obstacles. Each school shows a positive reflection in student attitudes and behavior that reflects the character values ​​taught, although challenges remain in the process of internalizing these values ​​in an era that continues to develop.The study highlights practical implications for enhancing character education. Schools are encouraged to integrate technology with localized cultural values, provide enhanced teacher training in digital pedagogy, actively involve parents, and establish community partnerships to address resource constraints. Policymakers must support efforts to align character education with the demands of the 5.0 era, ensuring its relevance and sustainability. This research offers valuable insights into how schools can adapt and innovate to embed character education effectively within the evolving educational landscape. By focusing on targeted strategies and addressing contextual challenges, educators and stakeholders can ensure the continued significance of character education in an era shaped by globalization and digital transformation.